THE PERCEPTION OF STUDENT AND TEACHER OF NETFLIX ENGLISH TO ENGLISH SUBTITLE: CORRELATING ENGAGEMENT, MOTIVATION, AND LISTENING ABILITY - Kurniawan, Bhagaskoro Ardhianto; Anwar, Khoirul (English Review: Journal of English Education, 2024)
This study examines the perceptions of students and teachers regarding the use of Netflix’s English-to-English subtitles to enhance engagement, motivation, and listening skills among intermediate EFL learners. Using a mixed-methods approach, quantitative data were gathered from 50 learners using structured questionnaires and listening evaluations, while qualitative insights were gained from interviews with three Universitas Airlangga graduates who teach EFL. A Structural Equation Modeling Partial Least Squares (SEMPLS) study found a high relationship between motivation and engagement, implying that motivated students actively participate in subtitled activities. Subtitles were proven to lower anxiety related with authentic hearing materials supporting Krashen’s Affective Filter Hypothesis theory, hence increasing engagement by making challenging subjects more approachable and enjoyable. Teachers underlined that subtitles improve students' confidence by offering a framework for comprehending complex dialogues and accents, progressively preparing them for real-world listening tasks. However, the SEMPLS model revealed a reduced direct association between involvement and listening performance, implying that subtitles alone may not entirely meet the requirements of standardized tests such as the TOEFL. Teachers suggested integrating subtitles with targeted listening activities to increase efficacy. This study focuses on the transformative function of Netflix subtitles in EFL learning, demonstrating their potential to boost motivation and engagement while also providing practical solutions for closing listening competence gaps.